Revision of the distribution of Suiriri suiriri burmeisteri (Aves: Tyrannidae) in the state of São Paulo, Brazil, with new records in its southeastern distribution limits - Macarrão, Arthur; de Godoy, Fernando Igor (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
The Suiriri Flycatcher (Suiriri suiriri) is widely distributed in South America, with the subspecies S. s. burmeisteri, which occurs mainly in Brazilian territory, restricted to the semi-open phytophysiognomies of the Cerrado, Caatinga, and Pantanal biomes. Due to the scarcity of records and information in the state of São Paulo, the species used to be previously considered as critically endangered. Here we present new records, some of which from further to the southeast than known for this state, and we briefly elaborate on its local distribution. Furthermore, we review the distribution of the species in the state of São Paulo.
Keywords: Cerrado; Suiriri flycatcher; Biome boundaries; Distribution map